Design and analysis of retaining structures for transformer stations in hilly areas - Che, Weixian; Zhu, Wenwei; Wang, Yanfeng; Guo, Jingen; Gao, Xin; Li, Lei; Zhang, Han; Li, Xiangyu (Frontiers in Materials, 2025)
IntroductionBased on a transformer station project, this paper conducts the design and analysis of retaining structures for transformer stations in hilly areas.MethodsAccording to the geological conditions and soil-rock properties combined with in-situ experiments and laboratory tests, the design parameters of the slope were obtained. The type of the retaining wall was calculated by using the arc sliding method, and the construction and monitoring of the slope project were elaborated. Meanwhile, an detailed and comprehensive discussion was conducted on the retaining methods in the construction of substations in hilly areas. The types of retaining structures adopted for slope supporting were summarized to provide reference and guidance for the design of transformer stations in backfill areas.ResultsThe safety factor varies greatly under different working conditions, and the most dangerous working condition is heavy rain.DiscussionSlope support in hilly areas is a scientific, rigorous and comprehensive technical work. The designer of the transformer station's slope should take into account local conditions, carefully consider the advantages and disadvantages, and have a thorough understanding of the site's topography, geology, and geotechnical characteristics.